Mechanisms of axon regeneration: The significance of proteoglycans - Sakamoto, Kazuma; Kadomatsu, Kenji (Biochimica et biophysica acta. General subjects, 2017)
Therapeutics specific to neural injury have long been anticipated but remain unavailable. Axons in the central nervous system do not readily regenerate after injury, leading to dysfunction of the nervous system. This failure of regeneration is due to both the low intrinsic capacity of axons for regeneration and the various inhibitors emerging upon injury. After many years of concerted efforts, however, these hurdles to axon regeneration have been partially overcome. This review summarizes the mechanisms regulating axon regeneration. We highlight proteoglycans, particularly because it has become increasingly clear that these proteins serve as critical regulators for axon regeneration. Studies on proteoglycans have revealed that glycans not only assist in the modulation of protein functions but also act as main players—e.g., as functional ligands mediating intracellular signaling through specific receptors on the cell surface. By regulating clustering of the receptors, glycans in the proteoglycan moiety, i.e., glycosaminoglycans, promote or inhibit axon regeneration. In addition, proteoglycans are involved in various types of neural plasticity, ranging from synaptic plasticity to experience-dependent plasticity. Although studies on proteins have progressively facilitated our understanding of the nervous system, glycans constitute a new frontier for further research and development in this field. This article is part of a Special Issue entitled Neuro-glycoscience, edited by Kenji Kadomatsu and Hiroshi Kitagawa. •Neuronal intrinsic pathways for axonal regeneration/sprouting after injury.•Intracellular/extracellular promoters/inhibitors for axonal regeneration•Proteoglycan and its neuronal cell surface receptors as major inhibitors